Nieważność małżeństwa z tytułów braku formy kanonicznej i przeszkody różności religii w kontekście sprawy spadkowej w świetle wyroku Roty Rzymskiej c. Alwan z dnia 22 października 2009 roku - Dzierżon, Ginter (Ius Matrimoniale, 2012)
The study presented by the author is a commentary on the sentence issued by of Roman Rota c. Alwan of 22 October 2009. In this case, the process of marriage annulment started on the grounds of lack of canonical form and disparity of cult. The rotal Turnus decided for the validity of the marriage since the regulations concerning the canonical form were met. During the trial, it was also proved that disparity cult dispensation was rightly granted.